2007
DOI: 10.1590/s0073-47212007000100005
|View full text |Cite
|
Sign up to set email alerts
|

Diet and microhabitat use by two Hylodinae species (Anura, Cycloramphidae) living in sympatry and syntopy in a Brazilian Atlantic Rainforest area

Abstract: ABSTRACT. We analyzed the diet and microhabitat use for two Hylodinae anurans (Cycloramphidae), Hylodes phyllodes Heyer & Cocroft, 1986 and Crossodactylus gaudichaudii Duméril & Bibron, 1841, living in sympatry at an Atlantic Rainforest area of Ilha Grande, in southeastern Brazil. The two species live syntopically at some rocky streams. The two species differed strongly in microhabitat use. Hylodes phyllodes occurred mainly on rocks, whereas C. gaudichaudii was observed mostly on the water. Regarding diet, col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 11 publications
4
15
1
Order By: Relevance
“…Crossodactylus bokermanni and B. saxicola were the species with the least overlap with the remaining species (but high overlap between themselves), mainly because they are independent of the vegetation strata for calling activities, using rocks and bare soil in the lower stratum. Other studies found significant degrees of spatial segregation in related species, such as syntopic hylodids (Hylodes phyllodes and Crossodactylus gaudichaudii), in permanent streams on the Atlantic Forest in southeastern Brazil (Almeida-Gomes et al, 2007). All these results corroborate the hypothesis that evolutionary history has little influence on patterns of microhabitat use by adult anurans, so that a small proportion of the existent variability can be explained by phylogenetic relatedness (Eterovick et al, 2010).…”
Section: Niche Breadth and Overlap Vs Number Of Coexisting Speciessupporting
confidence: 77%
“…Crossodactylus bokermanni and B. saxicola were the species with the least overlap with the remaining species (but high overlap between themselves), mainly because they are independent of the vegetation strata for calling activities, using rocks and bare soil in the lower stratum. Other studies found significant degrees of spatial segregation in related species, such as syntopic hylodids (Hylodes phyllodes and Crossodactylus gaudichaudii), in permanent streams on the Atlantic Forest in southeastern Brazil (Almeida-Gomes et al, 2007). All these results corroborate the hypothesis that evolutionary history has little influence on patterns of microhabitat use by adult anurans, so that a small proportion of the existent variability can be explained by phylogenetic relatedness (Eterovick et al, 2010).…”
Section: Niche Breadth and Overlap Vs Number Of Coexisting Speciessupporting
confidence: 77%
“…High niche overlap is usually reported for sympatric and syntopic anuran species, which is generally explained by the high prey availability and different foraging habits (Toft, 1981;Rosa et al, 2002;França et al, 2004; Gomes et al, 2007). In the present study, niche overlap among the four anuran species according to a randomised data matrix was higher than that expected by chance.…”
Section: Anuran Speciescontrasting
confidence: 41%
“…Although some species can be considered specialists (Simon and Toft, 1991;Santos et al, 2003;Biavati et al, 2004), anurans are usually reported as exhibiting generalist and opportunistic feeding habits (Schaefer et al, 2006;Almeida-Gomes et al, 2007;Araújo et al, 2007;Mahan and Johnson, 2007) and, as a result of that, studies on feeding habits have reported a high niche overlap among syntopic and sympatric anuran species (Toft, 1981;Rosa et al, 2002;França et al, 2004;Almeida-Gomes et al, 2007). For generalist anurans, aspects such as phylogeny, foraging mode, prey availability and abundance, and morphological constraints for capture and ingestion of a given prey type can be related to resource partitioning among species (Lima, 1998;Lima and Magnusson, 1998;França et al, 2004;Santos et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although most species in this biome have aquatic larvae (Becker et al ), not all of them have different terrestrial and breeding habitats. Stream‐dwelling amphibians (SDAs) in the Atlantic Forest are closely associated with flowing water in forested areas during their entire life cycle (Almeida‐Gomes et al ; Haddad et al ) and include all species of the genera Crossodactylus , Hylodes , Megaelosia , and most species of Cycloramphus (Haddad et al ). These species tend to be more affected by the loss of riparian forest because all their life stages (eggs, tadpoles, and adults) are strictly associated with small areas of a specific type.…”
Section: Atlantic Forest Stream‐dwelling Amphibiansmentioning
confidence: 99%